Instilling Nationalist Values from an Early Age Through the History of the Struggle of Indonesian Heroes - Yatmin; Etty Andyastuti; Anik Lestariningrum; M. Ipung Zainul Islam Sumarwoto (PT Inovasi Pratama Internasional, 2023)
Introducing the history of Indonesian independence to children is not an easy matter, considering that if you talk about history, what you definitely know is the long plot and events. Introduction to the history of Indonesian independence, in a fun way to foster good nationalist values in children from an early age. The aim is for young children to feel the meaning of struggle from simple actions. We know that children's learning methods must be adapted to their characteristics. The aim of the research will be to briefly describe how the introduction of stories of struggle increases the value of nationalism in children. The research design will use narrative/historical qualitative research, namely trying to find and describe narratively the activities carried out and the impact of the actions taken. This research will be carried out at the ABA VII Kindergarten, Kediri City with research subjects of 30 children aged 4-6 years. Collection techniques are observation, interviews and document analysis. Meanwhile, in analyzing the data, data triangulation, member checking and auditing techniques were used, as well as data analysis techniques according to Miles & Huberman, namely data reduction, data display and conclusions. The research results show that instilling nationalist values based on the story of the nation's struggle can be done through planning play activities starting from playing learning videos, designing Heroes' Day project activities and telling stories from books/pictures about the names of heroes as well as direct practice of visiting heroes' graves. Recommendations from research results should be developed other than during Heroes' Day so that we can see the continuity of children's understanding through activities to foster nationalism.